Pengaruh Tax Planning Dan Leverage Terhadap Nilai Perusahaan Dengan Transparansi Perusahaan Sebagai Variabel Moderasi: (Studi Empiris Pada Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2020) - Lusiyana Ika Pratiwi; Hari Stiawan (AKUA: Jurnal Akuntansi dan Keuangan, 2022)
The aims of the study are to examine and analyze the effect of tax planning and leverage on firm value with corporate transparency as a moderating variable. The type of research used in this study is a type of quantitative research. The data source used is secondary data, namely the annual report obtained from the Indonesia Stock Exchange (IDX). The population used in this study are property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2016-2020 period. The sample selection technique used purposive sampling technique and obtained as many as 12 companies for 5 years with a total sample data obtained was 60 sample data. The results of this study indicate that the tax planning variable has an effect on the firm value variable, the leverage variable has no effect on the firm value variable, the tax planning variable and leverage simultaneously affect the firm value, the corporate transparency variable is able to moderate by strengthening the effect of the tax planning variable on the firm value. company and the company's transparency variable can be moderated by strengthening the relationship between leverage and firm value.